The use of a single pass albumin dialysis for the management of liver failure - Azaševac, Tijana; Knežević, Violeta; Ćelić, Dejan; Ljubičić, Bojana; Lakić, Tanja; Mitić, Igor (Vojnosanitetski pregled, 2022)
Introduction. A single pass albumin dialysis (SPAD) is a form of extracorporeal liver support system for removing albumin-bound toxins and water-soluble substances that accumulate in liver failure (LF). Case report. We presented three patients hospitalized for LF and treated using the SPAD at the University Clinical Center of Vojvodina, Serbia, from 2018 to 2019.  Two of the patients presented with acute LF and one with acute-on-chronic LF. A total of 6 SPAD sessions were performed on each patient, resulting in decreased serum bilirubin and bile acid levels and hepatic encephalopathy grade. On discharge from the hospital, the liver function was improved in all the patients. Conclusion. SPAD removes the hepatotoxic substances without improvement of synthetic liver function. It represents a supportive treatment for LF patients who do not respond to the standard of care, offering a longer time for bridging to organ transplantation or spontaneous recovery of the liver function.
Keywords: albumins; liver failure, acute; regeneration; renal dialysis; treatment outcome.